Federated States of Micronesia : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2011)
This statistical appendix for the Federated States of Micronesia was prepared by a staff team of the International Monetary Fund as background documentation for the periodic consultation with wages. Consumer price index, Pohnpei consumer index, Chuuk consumer index, Kosrae consumer index, and Yap consumer index are also listed. Balance of payments for the years 2004-09 is also given. Interest rates of deposit money banks for 2004-09 are also given. External debt and debt service obligations are also listed.